A New Twist for Materials Science: The Formation of Chiral Structures Using the Angular Momentum of Light. Issue 14 (19th June 2019) - Omatsu, Takashige; Miyamoto, Katsuhiko; Toyoda, Kohei; Morita, Ryuji; Arita, Yoshihiko; Dholakia, Kishan
Abstract: Recent work has shown that irradiation with light possessing orbital angular momentum (OAM) and an associated phase singularity, that is an optical vortex, twists a variety of materials. These include silicon, azo‐polymer, and even liquid‐phase resins to form various helically structured materials. This article provides a review of the unique helical‐structured materials created and the novel fundamental phenomena enabled by this interaction between both the spin angular momentum and the OAM of light with matter. Such light‐induced helical‐structured materials will potentially lead to advanced photonic devices, for instance, metamaterials for ultrasensitive detection and reactions for chiral chemical composites. Abstract : Irradiation with light possessing orbital angular momentum and an associated phase singularity, that is an optical vortex, twists a variety of materials. Such light‐induced helical‐structured materials will potentially lead to advanced photonic devices, for instance, metamaterials for ultrasensitive detection and reactions for chiral chemical composites.